Recent Advances in Smart Manufacturing: A Case Study of Small, Medium, and Micro Enterprises (SMME) - K. A. Bello; M. G. Kanakana-Katumba; R. W. Maladzhi; C. O. Omoyi (Nigerian Journal of Technological Development, 2024)
The digital revolution is the future pathway to experiencing business evolution. It will be difficult for any organization to remain in business without deploying fourth industry revolution (4IR) techniques. This review guides prospective business owners on the need to embrace Smart Manufacturing (SM) timely and appropriate to enhance their business performance indicators. Many manufacturing companies are facing challenges in adopting SM tools in their organization due to a lack of essential resources despite the benefits associated with SM. Therefore, this study systematically reviewed the criteria evaluation techniques in implementing digital factories. This work has analysed small, medium, and micro enterprises (SMME), with the view to enumerate the appropriate criteria to determine the level of digital technology tools adoption framework. It also highlights how to compensate for the inadequate technical and financial resources in SM. The guidelines for SM implementation adoption in SMME is a research gap that was missing in previous studies. SM benefits, challenges, applications, significance, impact, and future perspectives, are discussed. Evaluation Criteria for SM Adoption practices were also expounded. The framework used in this study will help SMME owners to adopt SM.